2014
DOI: 10.1021/es5033426
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Extracellular Polymeric Substances on the Long-Term Fate, Dissolution, and Speciation of Copper-Based Nanoparticles

Abstract: ABSTRACT:The influence of phytoplankton-derived soluble extracellular polymeric substances (EPS), pH, and ionic strength (IS) on the dissolution, speciation, and stability of nano-CuO, nano-Cu, and Kocide (a micron sized Cu(OH) 2 -based fungicide) was investigated over 90 days. EPS improved the stability of commercial copper-based nanoparticles (CBNPs) in most conditions, in addition to influencing their dissolution. The dissolution rate was pH 4 ≫ pH 7 > pH 11. The presence of EPS correlated with higher disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
217
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 211 publications
(227 citation statements)
references
References 31 publications
5
217
0
1
Order By: Relevance
“…In addition to its surface charge, the tendency of Cu(OH) 2 to dissolve at low pH, 30,31 such as is found in the soil used in this study (Table 2), likely also contributes to its uptake behavior. Rhizosphere pH tends to be more acidic than the surrounding soil due to the release of protons by roots to stimulate and counterbalance the uptake of ions from the soil; 32 one effect of this acidity may be to dissolve a portion of the Cu(OH) 2 .…”
Section: Resultsmentioning
confidence: 86%
“…In addition to its surface charge, the tendency of Cu(OH) 2 to dissolve at low pH, 30,31 such as is found in the soil used in this study (Table 2), likely also contributes to its uptake behavior. Rhizosphere pH tends to be more acidic than the surrounding soil due to the release of protons by roots to stimulate and counterbalance the uptake of ions from the soil; 32 one effect of this acidity may be to dissolve a portion of the Cu(OH) 2 .…”
Section: Resultsmentioning
confidence: 86%
“…It is very likely that the large amount of production of ENMs will lead to their release into the environment through production, application, and disposal processes [1,22,23]. For example, titanium dioxide nanoparticles (TiO 2 NPs) were modeled and predicted to be discharged to the wastewater treatment plant, landfill and other environments [4,17,24].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…NOM is mainly the residual from plants and animals materials, as well as some of the biocolloids mentioned before [15,22,58]. NOM has been shown to interact strongly with ENMs [59], modifying their surfaces and in general making them more bioavailable [60,61].…”
Section: Biocolloid Geocolloid and Natural Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Although our data are from experiments in which we only considered the mitigating ability of algal-produced DOC, studies have shown that algal-produced DOC and natural organic matter share a lot of similarities in their composition and functional groups. 50,51 We defined "remediation" as the Cd and FeSSi concentrations either having no effect on the algae (exposure growth pattern was similar to the controls) or causing a "growth delay" ≤30 days. We explored the sensitivity of these remediation boundaries to model parameters by simulating the model 600 times with variations of parameters ±15% of the best fit parameter value and recorded the outcome (see SI Section 4 for details and Figures S16 and S17).…”
Section: Acs Nanomentioning
confidence: 99%